Design Aspect of including Infill Wall in RC Frame Design* - Sukrawa, M. (Institute of Research and Community Outreach - Petra Christian University, 2014)
This study compares analysis and design of a four story reinforced concrete (RC) frame structure with infill wall at upper levels and open at basement level. For the analysis, the RC frame are modeled as open frame (MOF) and infilled-frames using six compression only cross diagonal strut (MIF-Strut), and infilled frame using shell elements (MIF-Shell). Another model, MIF-Full, is created by adding walls at basement level of the MIF-Strut to study the effect of wall discontinuity. All three dimensional models are loaded with gravity load and quake load appropriate for South Bali region. Results show that the infilled-frame models are 4.8 times stiffer than MOF in the wall direction. Perpendicular to the wall, however, the stiffness increase is 29%. Soft storey mechanism exists in the absence of wall at basement level, regardless of reasonable column dimensions.